Sport experience is correlated with complex motor skill recovery in youth following concussion. Issue 9 (21st October 2019) - Dalecki, Marc; Gorbet, Diana J.; Macpherson, Alison; Sergio, Lauren E.
ABSTRACT: A previous study showed prolonged cognitive–motor integration (CMI) deficits in youth with a history of concussion who were classified as asymptomatic by current return-to-play protocols, highlighting potential differences between clinical symptom recovery and skill recovery. The present study examines factors that may influence skilled performance recovery (defined as matching the skill level of no-concussion history peers) post-concussion in a similar cohort. Sixty-four asymptomatic youth ( M = 13 yrs.) soccer, hockey, and lacrosse players with a concussion history ( M = 14 months post-concussion) who returned to play and sixty-two age-matched team members with no previous concussion participated in this study. They performed two touchscreen-based eye–hand coordination tasks, including a direct interaction and a CMI task. We analysed the relationship between CMI performance and concussion history, and whether age, sex, number of concussions, and years of sport experience in their sport affected skill recovery. Individuals with concussion history and higher amounts of sport experience (7–12 years) reached a performance level matching their no-history peers quicker (after 12 months) than those with concussion history and lower sport experience (1–6 years; recovery after 30 months). This effect was independent of the number of concussions, age, and sex. The present results point towards an important role of eye–limb coordination-related sport experience in functional CMI recovery post-concussion. Youth with a concussion history but greater sport experience may have more skill-related motor "reserve". This reserve may directly aid in behavioural recovery post-concussion, or the greater neurological efficiency associated with athletic experience provides a compensatory mechanism that provides faster functional recovery.